Pengaruh Aroma Terapi Chamomile Terhadap Pengurangan Kecemasan Pada Ibu Hamil Trimester III Di PMB Titik Ismawanti, SST Singosari - Metsi Indah Safitri; Sulistiyah (Journal of Innovative and Creativity, 2025)
Anxiety in third-trimester pregnant women is a common issue that can negatively affect both maternal and fetal health. Chamomile aromatherapy is known for its calming effects, which may help reduce anxiety levels. This research seeks to investigate the impact of chamomile aromatherapy on alleviating anxiety among pregnant women in their third trimester. A quasi-experimental method was utilized, incorporating a pretest-posttest design alongside a control group. A total of 35 third-trimester pregnant participants were randomly divided into intervention and control groups. The intervention group received chamomile aromatherapy for 15 minutes daily over 7 days, while the control group received no intervention. Anxiety levels were measured using. The analysis showed a significant reduction in anxiety levels in the group that received chamomile aromatherapy compared to the control group . Chamomile aromatherapy is effective in reducing anxiety in third-trimester pregnant women. It can be considered a non-pharmacological alternative to support maternal mental health during pregnancy.